Material complementar para o professor da rede SESI-SP de ensino : semelhança e software GeoGebra - Leite, Adriane de Oliveira (2015)
This research aims to propose activities for teachers using the Geogebra software, especially for teachers from the SESI-SP School Network in order to assist them in the teaching methodology, with teachers' work plan and, in addition, aiming to more significant and dynamic classes, in order to allow students reach their teaching and learning expectations, formulate valid arguments, make conjectures and justify their reasoning. The activities were applied by teachers of SESI-SP School Network to the students of 9th grade of elementary school, in anticipation of teaching and learning through “Similarity”, addressing Theorem of Thales, Metrics Relations in the Rectangle Triangle and Pythagoras Theorem. The results were analyzed and discussed, reporting the challenges and conclusions raised by the students during the activities while working with the Geogebra software and also based on the feedback provided by the teachers and the opinion of the analysts from SESI-SP School Network.